A study of the judicial approach by the Malaysian courts in dealing with child offender in murder and drugs offences / Adilah Azizan … [et al.] - Azizan, Adilah; Basir, Aina Affiyah; Azman, Fariza Amira; Mazelan, Nur Ain Sofiah (2014)
This research looks at the judicial approaches by the Malaysian Courts in dealing with child offenders on murder and drug cases. The goal is to suggest several recommendations in order to improve the current sentencing practice for child offenders. This has been done by analysing decided cases on murder and drugs involving child offenders in Malaysia and comparing the juvenile justice system in Malaysia with the system in New Zealand. The information was obtained mostly from legal textbooks and online journal articles. Two interviews were also conducted to the first and second respondent. Upon analysing these findings, several recommendations were made which are reforming the administration of Courts for Children and improving the consistency in sentencing practices and restorative justice. Through showing that the judicial approach taken in dealing with child offenders need to be different from the adult offenders, this research highlights the importance for the rights of the child offenders as children are not violated.